Affective Video Games: A Systematic Mapping Study - Rico Olarte, Carolina (2019)

Framework for data model to personalized health systems - Rico Olarte, Carolina (2016)

HapHop-Physio: a computer game to support cognitive therapies in children - Rico Olarte, Carolina; López, Diego M.; Narvaez, Santiago; Farinango, Charic D; Pharow, Peter S (Psychology Research and Behavior Management, 2017)
Background: Care and support of children with physical or mental disabilities are accompanied with serious concerns for parents, families, healthcare institutions, schools, and their communities. Recent studies and technological innovations have demonstrated the feasibility of providing therapy and rehabilitation services to children supported by computer games. Objective: The aim of this paper is to present HapHop-Physio, an innovative computer game that combines exercise with fun and learning, developed to support cognitive therapies in children. Methods: Conventional software engineering methods such as the Scrum methodology, a functionality test and a related usability test, were part of the comprehensive methodology adapted to develop HapHop-Physio. Results: The game supports visual and auditory attention therapies, as well as visual and auditory memory activities. The game was developed by a multidisciplinary team, which was based on the Hopscotch® platform provided by Fraunhofer Institute for Digital Media Technology IDMT Institute in Germany, and designed in collaboration with a rehabilitation clinic in Colombia. HapHop-Physio was tested and evaluated to probe its functionality and user satisfaction. Conclusion: The results show the development of an easy-to-use and funny game by a multidisciplinary team using state-of-the-art videogame technologies and software methodologies. Children testing the game concluded that they would like to play again while undergoing rehabilitation therapie
Keywords: Computer game; Exer-games; Cognitive therapies; Rehabilitation

Objective Method for User Experience Evaluation of Children with SLD on HapHop-Physio - Rico Olarte, Carolina (2018)

Towards a conceptual framework for the objective evaluation of user experience - Rico Olarte, Carolina; López, Diego M.; Kepplinger, Sara (Lecture Notes in Computer Science - LNCS 10918 Design, User Experience, and Usability Theory and Practice, 2018)
Background: The concept of user experience (UX) involves many aspects and different perspectives, making it difficult to evaluate the whole set of what UX represents. Despite existing standards, a clear definition of the UX evaluation concerning the identification of the different aspects to be evaluated according to the perspectives forming the UX (user and system), taking into account a given context of use is missing. Objective: Propose a conceptual framework for identifying differences between the UX evaluation perspectives and their measurable aspects. Methods: We followed a qualitative method for building conceptual frameworks. Results: The proposed conceptual framework identifies and associates the main UX concepts, from the user and system perspectives. The obtained plane of concepts provides a better overview of the phenomenon studied. The built framework led to the definition of an objective UX evaluation method: physiological signals are the convergence point between the physical state of the user and the measurement of emotions. Conclusion: The evaluation of UX is particularly important in ICT solutions for health since users/patients must maintain the motivation to continue using technology, in order to guarantee adherence to their treatments or interventions. The obtained framework and method are the first step towards finding suitable and according-to-context UX evaluation processes allowing an improved interaction between user and syste
Keywords: User experience; Conceptual framework; Evaluation methods; Objective evaluation

Towards a Standardized User Model for Personalized Systems in Health - Rico Olarte, Carolina; Giron Buitron, Edwar Javier; Ceron Rios, Gineth Magaly; Lopez Gutierrez, Diego Mauricio (Sistemas y Telemática, 2015)
The definition of a user model supports personalization in computer-based systems. For a personalized system in health, which supports the promotion of healthy habits and lifestyles, in particular physical activity and healthy diet, a user model according to the ISO/TR 14292 standard for Personal Health Records [PHR] is proposed. The description of the standardized user model includes: a characterization of the user model; the proposed user model according to the ISO standard; the relationships and inferences of the user model; and reference architecture for the system to be developed. Finally, a prototype with a small dataset is implemented and some possible mockups supporting the proposed architecture are designed.
Created from Fastlane, WoS look-up

User Experience Evaluation Methods in Games for Children with Cognitive Disabilities: A Systematic Review - Rico Olarte, Carolina (2017)

User experience evaluations in rehabilitation video games for children: a systematic mapping of the literature - Rico Olarte, Carolina (2017)